The Effect Of Strengthening HR Competencies and Customer Relationship Management (CRM) on Customer Service Performance with Training as an Intervening Variable in PLN UID Aceh - Agus Susanto; Hernawaty (CV. Doki Course and Training, 2026)
The purpose of this study was to investigate how Human Resource Competency Improvement and Customer Relationship Management (CRM) influence Customer Service Performance, with Training as a mediating factor at PLN UID Aceh. This study used a sample of 140 participants selected through purposive sampling. The analysis was conducted using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results showed that Human Resource Competency Improvement and Customer Relationship Management both had a positive and significant effect on Training. Furthermore, Training was found to have a positive and significant effect on Customer Service Performance. Furthermore, Customer Relationship Management directly influences Customer Service Performance, while Human Resource Competency Improvement has no direct effect but rather an indirect effect through Training as an intermediary factor. These results highlight the important role of Training in improving customer service performance by enhancing human resource competencies and implementing effective CRM strategies.